Pengaruh Model Project Based Learning terhadap Aktivitas dan Hasil Belajar Peserta Didik Kelas X SMA - Anugrahsari, Iin; Adnan, Adnan; Junda, Muhammad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The purpose of this study was to investigate the effect of project-based learning models on students' learning activities and outcomes. This research employed a quasi-experimental design with a pretest-posttest control group. The study was conducted from July to August 2022 at SMA Negeri 12 Makassar. The population consisted of 10th-grade students in the science program, totaling 7 classes. Random sampling selected X MIA 4 as the experimental group and X MIA 2 as the control group. Observational sheets were used to monitor student activities, while test instruments were used to assess student learning outcomes. Data collected were analyzed using descriptive statistics and inferential statistical analysis through Statistical Package for Social Science (SPSS) Version 23.0. Analysis of pretest and posttest scores from the experimental group, comprising 34 students, revealed that 5 students achieved a score in the 'very good' category and 9 students in the 'good' category. In contrast, the control group did not have any students in the 'very good' category; only 3 students were in the 'good' category. Observational results from three observers in the experimental group indicated that 96.73% of students were 'highly active', whereas in the control group, 67.07% were 'sufficiently active'. In conclusion, the research findings suggest that the project-based learning model influences students' learning activities and outcomes.